Factores socioculturales condicionantes de la dependencia económica de las mujeres amas de casa residentes en la comuna San Agustín - Sánchez Sánchez, Diana Gabriela; Yépez Cedillo, Vilma Carolina (Machala: Universidad Técnica de Machala, 2021)
The economic dependence of women is a phenomenon that has emerged throughout history in a global perspective, has been deployed in all social and economic spheres to be presented as a widespread problem where there are new forms of coexistence. In this context, the present research work is developed with the modality of an integrating project, in effect, it studies the socio-cultural factors that condition the economic dependence of housewives residing in the San Agustin commune. This fact is manifested as a product of an economy that has not been liberated from a prevailing patriarchal order in the community, which causes an offense towards domestic work, being this a fundamental element in the current mercantile dynamics, orienting women in a situation of labor damage in front of men. The problem has been raised in a systematized manner through the following research question. What is the significance of socio-cultural practices in the economic dependence of housewives in San Agustín in the Santa Rosa canton Therefore, the main objective is to determine the transcendence that sociocultural practices have on the economic dependence of housewives in San Agustín of the Santa Rosa canton. The object of study is inscribed in the normative regulations of the Technical University of Machala, in the domain Education, Equity and Citizenship and with its respective line of research Social Equity and Citizen Organization, corresponding to the degree of Sociology. The research is based on the theories of gender and feminism as sociological currents, applying the qualitative approach and as research techniques were used, the interview and the execution of a focal group that were applied to qualified informants representative of the environment, as well as members of the neighborhood committee and professionals who work in the commune, finally the survey was executed to housewives as key actors in the research, therefore it was possible to collect the necessary data for the work. Among the results obtained, it was determined that housewives carry out productive activities that generate low income. In addition to this fact, the few working days vary between one and two days, making work precarious. In addition, it was detected as a serious socio-cultural factor the imposition of machismo as an expression of a patriarchal society that has limited the independence of women, establishing negative behaviors that minimize, discriminate and exclude the female by subjecting her to the dominance of men. After the diagnostic study, an integrative proposal was developed. Training program for the inclusion of the housewife resident in the San Agustín commune in the development of the productive microenterprise sociofamily enterprise, with the purpose of designing eight training courses-workshops for housewives, where they aspire to an active and dynamic participation in the different planned activities, All this with the firm intention of promoting individual or associative inclusion in the world of microenterprise, family and community entrepreneurship, allowing them to improve their social and economic status, contributing in a decisive way to the integral development of the San Agustin community.
La dependencia económica de la mujer es un fenómeno que ha surgido a lo largo de la historia en perspectiva mundial, se ha desplegado en todas las esferas sociales y económicas por presentarse como una problemática generalizada donde existen nuevas formas de convivencia. En dicho contexto se desarrolla el presente trabajo de investigación con la modalidad de proyecto integrador, en efecto se estudia los factores socioculturales condicionantes de la dependencia económica de las mujeres amas de casa residentes en la comuna San Agustín. Este hecho se manifiesta como producto de una economía que no se ha liberado de un orden patriarcal prevalecido en la comunidad por lo cual, ocasiona una ofensa hacia el trabajo doméstico siendo éste un elemento fundamental en la dinámica mercantil actual, orientando a la mujer en una situación de perjuicio laboral frente al hombre. Se ha planteado de manera sistematizada el problema a través de la siguiente pregunta de investigación. Qué trascendencia tienen las prácticas socioculturales en la dependencia económica de las mujeres amas de casa en San Agustín del cantón Santa Rosa Por ende, el objetivo principal es determinar la trascendencia que tienen las prácticas socioculturales en la dependencia económica de las mujeres amas de casa en San Agustín del cantón Santa Rosa. El objeto de estudio se inscribe en el reglamento normativo de la Universidad Técnica de Machala, en el dominio “Educación, Equidad y Ciudadanía y con su respectiva línea de investigación Equidad Social y Organización Ciudadana, correspondiente a la carrera de Sociología. La investigación se fundamenta en las teorías de género y feminista como corrientes sociológicas, aplicando el enfoque cualitativo y como técnicas de investigación se emplearon, la entrevista y la ejecución de un grupo focal que fueron aplicadas a informantes calificados representativos del medio, como a miembros del comité barrial y profesionales que laboran en la comuna, por último la encuesta se ejecutó a las mujeres amas de casa como actoras claves de la investigación, por lo tanto se logró recopilar los datos necesarios para el trabajo. Dentro de los resultados obtenidos se determinó que las mujeres amas de casa realizan actividades productivas generadoras de bajos ingresos económicos. A este hecho se suma los pocos días laborados que oscila entre uno a dos días, evidenciándose precariedad laboral. Además, se detectó como factor sociocultural grave la imposición del machismo como expresión de una sociedad patriarcal que ha coartado la independencia de la mujer, instaurando conductas negativas que minimiza, discrimina y autoexcluye a la fémina sometiéndola al dominio del hombre. Posterior al estudio diagnóstico se elaboró la propuesta integradora denominada: Programa de capacitación para la inclusión de la mujer ama de casa residente en la comuna San Agustín al desarrollo del emprendimiento productivo microempresarial sociofamiliar, con el fin de diseñar ocho cursos-talleres de capacitación a la mujer ama de casa, en donde se aspira una participación activa y dinámica en las diferentes actividades planificadas, todo ello en la firme intencionalidad de fomentar inclusión individual o asociativa en el mundo del emprendimiento microempresarial, familiar y comunitario, permitiéndoles a su vez mejorar su status social y económico, contribuyendo de manera decidida al desarrollo integral de la comunidad San Agustín.
Keywords: DEPENDENCIA ECONOMICA; MUJER; FACTOR SOCIOCULTURAL